Sumoylation of Turnip mosaic virus RNA Polymerase Promotes Viral Infection by Counteracting the Host NPR1-Mediated Immune Response - Cheng, Xiaofei; Xiong, Ruyi; Li, Yinzi; Li, Fangfang; Zhou, Xueping; Wang, Aiming (The Plant cell, 2017)
Sumoylation is a transient, reversible dynamic posttranslational modification that regulates diverse cellular processes including plant-pathogen interactions. Sumoylation of NPR1, a master regulator of basal and systemic acquired resistance to a broad spectrum of plant pathogens, activates the defense response. Here, we report that NIb, the only RNA-dependent RNA polymerase of (TuMV) that targets the nucleus upon translation, interacts exclusively with and is sumoylated by SUMO3 (SMALL UBIQUITIN-LIKE MODIFIER3), but not the three other SUMO paralogs. TuMV infection upregulates SUMO3 expression, and the sumoylation of NIb by SUMO3 regulates the nuclear-cytoplasmic partitioning of NIb. We identified the SUMO-interacting motif in NIb that is essential for its sumoylation and found that knockout or overexpression of SUMO3 suppresses TuMV replication and attenuates viral symptoms, suggesting that SUMO3 plays dual roles as a host factor of TuMV and as an antiviral defender. Sumoylation of NIb by SUMO3 is crucial for its role in suppressing the host immune response. Taken together, our findings reveal that sumoylation of NIb promotes TuMV infection by retargeting NIb from the nucleus to the cytoplasm where viral replication takes place and by suppressing host antiviral responses through counteracting the TuMV infection-induced, SUMO3-activated, NPR1-mediated resistance pathway.